Distance learning in crises (opportunities and challenges) from the point of view of male and female teachers in Hafar Al-Batin Province - Akhdhir, Mansour Abdullah (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the advantages of distance education and the challenges that hinder its success in the Kingdom of Saudi Arabia in light of the Corona pandemic crisis from the viewpoint of male and female teachers in the public education sector in Hafar Al-Batin Governorate in the Kingdom of Saudi Arabia. The researcher used the descriptive and analytical method, and the tool consisted of a questionnaire consisting of (19) items distributed in two areas: challenges and advantages. It was distributed to a random stratified sample of (110) male and female teachers in the public education sector in Hafar Al-Batin Governorate in the Kingdom of Saudi Arabia. The results of the research showed that the field of advantages and opportunities provided by distance learning obtained a large arithmetic average of (3.43), while the degree of agreement of the sample on the field of challenges facing distance education was medium with an average of (3.20). The results showed no statistically significant differences at the level of significance (α ≤0.05) among the means of the research sample estimates of the advantages and challenges of distance education and learning in light of the Corona pandemic crisis. In the end, the researcher recommended the necessity of using distance learning in the programs of the Ministry of Education, training teachers and developing their skills in using computers and extracting information from information networks.